Relaciones afortunadas y descubrimientos siniestros: en torno a la descendencia francesa de Juan Montalvo (Crítica) - Velecela Chacón, Juan Salvador (2024)
Through the figure of Jean Contoux, the Parisian son of Juan Montalvo, this article traces the career of renowned Ecuadorians, such as the diplomats Víctor Manuel Rendón, the brothers José and Miguel Seminario, and Enrique Dorn y de Alsúa, who, in their time, were linked to French cultural or political history.